Amor à camisa? : conciliando razão e paixão no ambiente do futebol profissional - Alves, Fábio Padilha (2010)
We notice that the rationalization of practices that involve the professional soccer in Brazil has been more present, mostly intensified after the release of the law number 9615/98 (“Pelé Law”). This way, we have seen the insertion of business elements on clubs administration, which have transformed this sport into a great business. Another important characteristic of professional soccer, intensified in Brazilin the past years, is the great turnover of players, favored by the heating of the foot labor market. Especially motivated by professional matters – salary, working conditions and visibility – the athletes face apparent new scenery on the relations that involve soccer: the necessity to conciliate their own interests and the passion of the fans. So, there is a field of tensions inside opposing logics in which the athletes need to know how to deal with. So, this work aims at investigating the existence of such tensions on professional soccer, checking how the athletes build mediation strategies for the tensions that involve the rationality of the professional practice and the fans’ passion. In order to accomplish so, nine professional and former athletes who played in different clubs during their careers were interviewed. Through this research we have noticed that this commodification of soccer decisively influences the relation between athletes, fans and clubs. In this context, it must be detached the fact that players consider it important to stay a longer period in a club, claiming that this is a fundamental condition to create affective bonds, to participate on the community imagined by the fans and become an idol. However, due to ease salary gains that arise from transactions, the same players prefer to “slue around” instead of remaining at a club. In summary, we can say that the attempts of conciliation which were mapped do not mean a cold attitude or a negation of the practice, rational dimension of professional soccer, but a specific elaboration, necessary for a practice that, even in its professional dimension, seems to resist to rationalization